Edukasi dan Pelatihan Inovasi Pangan Lokal: Pembuatan Bakso Tempe Ikan Kembung (BATIK) Upaya Meningkatkan Gizi Anak - Milka Putri Novianingrum; Lusiawati Dewi (Jurnal Pengabdian Masyarakat, 2025)
Community service activities through education and training on the production of Tempe Mackerel Fish Meatballs (BATIK) were carried out at YPAC Semarang as an effort to improve children’s nutrition and prevent stunting. The background of this activity departs from the still low consumption of fish in Semarang City and the lack of public understanding of the importance of animal and vegetable proteins for children’s growth and development. The methods used include educational lectures, interactive discussions, and training on the production of BATIK using local food. A total of 30 participants, consisting of pregnant women, housewives, and community leaders participated in a series of activities. The results of the pretest showed that only 35% of participants knew the food source of protein, while the posttest results increased significantly until 90% of participants were able to answer correctly. In addition to increasing knowledge, there was a change in the attitude of the participants to pay more attention to family nutrition. BATIK products have a high content of animal and vegetable proteins, are nutritious, affordable, and have the potential to become local food innovations. Therefore, this activity has demonstrated its effectiveness in enhancing public knowledge and in providing healthy food alternatives that contribute to stunting reduction efforts in Semarang City.